COMPETENCY AND QUALITY OF FINANCIAL REPORTING MANAGEMENT OF BLUD HOSPITALS IN WEST JAVA PROVINCE: Calidad y competencia de gestión de informes financieros de los hospitales BLUD en la provincia de Java Occidental - PUSPITASARI, R.; YADIATI, W.; WINARNINGSIH, S.; IRIYADI, IRIYADI (Utopía y Praxis Latinoamericana, 2021)
This study aims to empirically prove whether the competency of financial reporting managers positively affects the financial statements’ quality and performance accountability. Data were collected from questionnaires and interviews conducted at a number of BLUD hospitals in West Java Province and analyzed using SEM-PLS. from the returned questionnaires of 96 respondents, and the results show that the competency of financial reporting managers has a direct positive effect on the quality of financial statements but has no effect on performance accountability. But, the quality has a positive effect on performance.